KHAZANAH SAINS DAN MATEMATIKA DALAM ISLAM - Rizqon Halal Syah Aji (SALAM: Jurnal Sosial dan Budaya Syar-i, 2014)
Abstract: Treasures of Science and Mathematics in Islam. Islam is the religion of the civilized. Islam is not just a religion, but a civilization that can be discerned by empirical (teachings) of the progress of human civilization, as well as the subject of the passage of a civilization. Islam has a treasures science and mathematics that have been claimed by the West as a civilization biggest contribution to science. Muslim scholars contribute ideas to the development of science and mathematics cannot be considered minor and denied. Postulates a positive relation of the essence of mathematics is not separated from the phenomenology of the Qur'an will be a proof on the monotheism. The role of Muslim scientists contributed ideas and findings on various things in the science and math adds proof that no dichotomy between religion and science. Phenomenology teachings of monotheism also provide evidence that the positive relationship between revelations against rationality is not mutually contradictory. Keywords: Science, Mathematics, Muslim Scientist, Phenomenology Abstrak: Khazanah Sains dan Matematika Dalam Islam. Islam merupakan ajaran agama yang beradab. Islam bukan sekedar agama, namun peradaban yang dapat dicerna secara empirik (ajaran) terhadap kemajuan peradaban manusia, sekaligus subjek dari berjalannya sebuah peradaban. Islam mempunyai khasanah sains dan matematika yang selama ini diklaim oleh Barat sebagai sumbangsih terbesar peradabannya dalam ilmu pengetahuan. Sumbangsih pemikiran sarjana Muslim terhadap perkembangan sains dan matematika tidak bisa dianggap kecil dan dinafikan. Relasi positif dari esensi postulat dalam matematika tidak lepas dari fenomenologi Alquran yang memberikan pembuktian akan sebuah nilai ketauhidan. Peran ilmuwan Muslim memberikan kontribusi pemikiran dan temuan atas berbagai hal dalam sains dan matematika menambah pembuktian bahwa tidak adanya dikotomi antara agama dan ilmu pengetahuan. Fenomenologi ajaran tauhid juga memberikan relasi positif terhadap pembuktian bahwa antara wahyu dengan rasionalitas tidak saling bertentangan. Kata kunci: sains, matematika, ilmuwan Muslim, fenomenologiDOI:10.15408/sjsbs.v1i1.1534